Managing technology : A case study on the cost reduction of the molding assembly process in the semiconductor industry - Kaliyappan, Renganathan (2014)
The aim of this study is to investigate the ways in which the semiconductor industry can provide high-quality integrated circuit (IC) assembly services to satisfy customer needs and help companies introduce new products to the market in the shortest time possible. In this study, prototype ICs are assembled in production volumes that not only meet design requirements but also provide quality samples to customers. To increase the cost effectiveness of the component assembly process, the cost of the existing process was determined and a mathematical formula developed to predict the outcome of changes applied in the process (Ragona, 2002). Over the years, the performance of the semiconductor chip has been significantly improved to meet the current market demand for electronics devices, such as smartphones, personal computers, and car navigation systems. The transistor is the main component of the semiconductor chip. Therefore, the performance of the transistor is important because it significantly influences the density of the transistor per chip (Gordon, 1965). An increase in the capacity of the transistor per chip increases the manufacturing cost. For this case, various methods and strategies have been implemented to ensure that chip suppliers remain competitive in the market. This research used the high density substrate approach to analyzed the cost of assembly and molding profit through the models which were developed from economics theory of the firm models namely the average cost model and the profit model by integrated in the molding technology aspect particularly the high density substrate. The new models which were developed by the author are the Molding Assembly Cost Model (MACM) and the Molding Assembly Profit Model (MAP). 4 hypotheses were developed to compare the high density substrate versus the low density substrate. The hypotheses for this comparison are the throughput, the yield, the assembly cost and finally the profit. The author concluded that the high-density substrate approach is sufficient to guarantee of the assembly cost reduction hence improvement of the profit with the condition that the assembly yield must remain stable.